2019
DOI: 10.3390/su11082201
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as An Approach to Promote Tourist Recycling Behavior

Abstract: Recycling behavior is an issue that affects the sustainability of many seasonal destinations. The EU promotes projects such as the UrbanWaste that try to study how to avoid the deplorable consequences on cities of this situation. This project has implemented a gamified application, named WasteApp in several European cities, in order to promote the recycling behavior of tourists. This study aimed to verify if the application can be a successful tool to foster recycling and to improve tourism destination reputat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 60 publications
1
38
0
1
Order By: Relevance
“…In an intervention designed to increase recycling behavior, tourists were encouraged to use an app called "WasteApp" to locate recycling bins in several cities [48]. "WasteApp" was effective at increasing recycling for users who perceived the app as useful.…”
Section: Waste Management and Water Conservationmentioning
confidence: 99%
“…In an intervention designed to increase recycling behavior, tourists were encouraged to use an app called "WasteApp" to locate recycling bins in several cities [48]. "WasteApp" was effective at increasing recycling for users who perceived the app as useful.…”
Section: Waste Management and Water Conservationmentioning
confidence: 99%
“…Although not directly related to the effect of gamification, Yoo et al's study [41] investigated which factors affect the adoption of gamified applications within the context of tourism, and found that the hedonic characteristics of gamified apps are strong. By adopting TAMs (Technology Acceptance Models), Aguiar-Castillo et al [42] verified the perceived usefulness and ease of use on tourist satisfaction levels and recycling behavior. Within the context of tourism, few studies have paid attention to empirical evidence of the effect of gamification on behavioral models, Thus, this study tries to develop a theoretical model of gamification to explore its impact on psychological and behavioral outcomes in a comprehensive process, based on a field experiment employing a newly-developed gamified app tailored for the Gyeongbok palace, a cultural heritage site.…”
Section: Gamification In the Tourism Contextmentioning
confidence: 99%
“…Within the articles published between 2018-2019 it was possible to identify various that relate to the same solution, like "MUV" [59,61] and GoEco! [51,57] for transportation choices, and WasteApp [69,74] for tourist behavior, providing a comprehensive picture of the rationale behind the apps, their features, indicators, and early results of the testing and monitoring sessions.…”
mentioning
confidence: 99%